Peran Pembiayaan Hijau (Green Financing) dalam Mendorong Green Economy di Sektor Usaha Mikro, Kecil, dan Menengah di Sumatera Utara dengan Produk Ramah Lingkungan Sebagai Variabel Mediasi - Harahap, Hastuti Handayani; Rajagukguk, Frederick Rudy Sentosa; Arifin, Indra Welly (Economic Development Progress, 2024)
This research is about the role of green financing in encouraging the green economy in the micro, small and medium business sector in North Sumatra with environmentally friendly products as a mediating variable. This research design uses a quantitative approach which aims to measure and test the relationship between variables statistically. Data collection was carried out through a questionnaire designed to obtain information about the use of green financing, production of environmentally friendly products, and implementation of green economic practices by MSMEs. Quantitative research method with a PLS-SEM approach to analyze the relationship between green financing and the green economy with environmentally friendly products as a mediating variable. The research results of the first hypothesis are accepted that Green Financing (X) has an effect on the Green Economy (Y). The second hypothesis is accepted that Green Financing (X) influences Environmentally Friendly Products (Z). The third hypothesis is accepted that Environmentally Friendly Products (Z) influence the Green Economy (Y). The fourth hypothesis is accepted that Green Financing (X) has a significant effect on the Green Economy (Y) through Environmentally Friendly Products (Z) as an intervening variable.